Investigating the Relationship Between Service Quality and Student Intention Behavior in Higher Education Service Experience - Windasari Windasari; Ainur Rifqi; Aditya Chandra Setiawan; Shelly Andari; Ahmad Abdullah Zawawi; Noor Akhmarisha binti Saari (Universitas Pendidikan Mandalika, 2024)
This study aims to investigate the relationship between service quality and student intention behaviour in Higher Education Institutions. This research used a correlational method with a quantitative approach. The online questionnaire was distributed to 110 State University of Surabaya students following the cluster random sampling. In this research, data gathered was analyzed using the Pearson Product Moment correlation analysis. The results showed a significant positive correlation between higher education service quality and student intention behavior. The better service quality provided linier withlinearnt intention behavior fobehaviourending and their intention to loyal in in the institutton. This study's findings remind us to improve the quality dimension as a key factor in attracting and retaining students to student education Institutions.